Visitor segmentation in alpine tourism: Evidence from a survey-based cluster analysis in northern Italy - Francesca Visintin; Elisa Tomasinsig; Laura Pagani; Ivana Bassi; Vanessa Deotto; Lucia Montefiori; Luca Iseppi (Journal of Mountain Science, 2026)

Consumer attitudes towards the mountain product label: Implications for mountain development - Ivana Bassi; Matteo Carzedda; Luca Grassetti; Luca Iseppi; Federico Nassivera (Journal of Mountain Science, 2021)
To protect and promote the originality and authenticity of mountain foodstuffs, the European Union set Regulation No 1151/2012 to create the optional quality term “mountain product”. Our research aimed at exploring the attractiveness of the mountain product label for consumers, considering both attitude towards the label itself and purchase intentions. We propose a model to investigate relationships between four latent constructs — mountain attractiveness, mountain food attractiveness, attitude towards the mountain product label, and purchase intention — which have been tested, thus confirming the statistical relevance of the relationships. All 47 items selected for describing the latent constructs are suitable for this purpose. Ridge and LASSO results also show that 17 items of the first three constructs are relevant in explaining purchase intentions. Some contextual variables, such as age, income, geographical origin of consumers, and knowledge of mountain products and mountains for tourism purposes, can positively influence consumers’ behavior. These findings could support the design of mountain development strategies, in particular marketing actions for both the product and the territory.